Outline Technique in Teaching Writing Skill at MTS Negeri 1, Morotai Island - Megawati Basri; Rina Wahyuni; Gullty Karlos Papingka; Ledy Yanti Lessy (East Asian Journal of Multidisciplinary Research, 2023)
Writing is one of the skills in English. It should be learned for the students because they have to produce the text in English. Some students face any problems in learning and practice of writing skill. For this case, the researchers found the solution in students writing. the teacher should be creative and innovative in teaching writing because in this part, the teacher has the big role to make the students know how to write in a good way. The researchers applying the outline technique in teaching writing. Outline technique is the technique that used for the students to organize the idea and arrangement of the idea and pour into the text. The aim of this research is to know whether the students improve their writing skill in using outlining technique or not, and what is the problem that face by the students when applying this technique. This research is happened in MTs State 1 of Morotai Island. This research is quantitative research using T-test which is the result show that the score was 0.755 and it was higher that r table 0.367. it can be said that the data is accepted. The result of this result is the application of outline technique improve the students’ writing skill.